Specjalne strefy ekonomiczne (SSE) na Dolnym Śląsku i ich wpływ na promocję regionu i rynek pracy - Adamczuk, Franciszek (Special Economic Zones in Lower Silesia and their Influence on the Region Promotion and Labour Market, 2005)
Special economic zones (SSE) in Lower Silesia and their influence on the promotion of the region and on the labour market. This article concerns Special Economic Zones (SSE) in Lower Silesia. The Author of the article has shown the importance of SSE and their impact on two domains : the promotion of the region and the regional labour market. In the final part of the article, previous effects of SSE and conclusions from the issue have been analyzed and summarized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 11-19